HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PENDERITA HIPERTENSI DIET RENDAH GARAM DI PUSKESMAS SIBUHUAN - Nasution, Lisna Khairani; Rambe, Normayanti (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Family support is needed by patients with hypertension in overcoming their problems that occur during long-term treatment. Hypertensive patient compliance determines the success of treatment programs. This study was descriptive koleratif that aims to analyze the relationship between family support with client adherence of hypertensive patients in the low-salt diet Sibuhuan Puskesmas Padang Lawas. This study was conducted in February 2021 to 41 hypertensive patients. Sampling was done by sampling incidental. The results of data analysis showed that the majority of patients with hypertension have a good family support as many as 24 people (58.5%), and non-adherent low-salt diet were 28 people (68.3%). The results showed that family support variable has a value significancy (p) is 0.021 (p <0.05), which means no family support relationships with clients adherence of patients a diet low in salt. It is suggested to the nurse and the family in particular in order to motivate and support of hypertensive patients to comply with treatment programs.